Tingkat Kecemasan terhadap Kematian pada ODHA - Ahdiany, Gina Nur; Widianti, Efri; Fitria, Nita (Jurnal Keperawatan Soedirman, 2017)
One of the psychological impact suffered by PLWHA after HIV-AIDS was death anxiety. Excessive death anxiety would cause emotional function disorder such as neurotic, depression, and psychosomatic disorders. The purpose of research was to describe the level of death anxiety in PLWHA in Cilincing Puskesmas North Jakarta. The research was quantitative descriptive. The population was PLWHA in Puskesmas Cilincing. The samples were 30 respondents with consecutive sampling technique. The instruments used were Templer Death Anxiety Scale had done the validity test with the results of a range of values from 0.30 to 0.74 and test the reliability of 0.734. Univariate data were analyzed by frequency distribution. The results of this analysis, it is known that more than half of respondents (56.7%) had high death anxiety, and almost half of respondents (43.3%) had low. It could be concluded that the newly diagnosed PLWHA over the past year to experience anxiety about the high mortality.